Knowledge and stress level in pregnant women: A cross-sectional study during the COVID-19 pandemic - Kusumo, Maria Priliantari Ayu; Wijaya, Yosi Maria; Susilowati, Yuanita Ani (Universitas Airlangga, 2024)
Introduction: Pregnant women are vulnerable to COVID-19 due to weakened immunity, leading to heightened stress amidst uncertainties about its impact. Research indicates increased levels of depression, stress, and anxiety in pregnant women since the pandemic declaration. This study explores the link between COVID-19 knowledge and stress levels among pregnant women.Methods: Data collection involved the administration of a questionnaire addressing COVID-19 knowledge and stress levels. A total of 255 respondents voluntarily participated in the study. Quantitative methods were utilized, employing a descriptive correlation design within a cross-sectional approach. The accidental sampling technique was used to select participants.Results: Univariate analysis results obtained 78.4% have a good knowledge, and 40.4% experienced moderate stress levels. Bivariate analysis using the Spearman rank indicated a relationship between knowledge and stress levels (P-value <0.001, r 0.732).Conclusions: The study proposes that hospitals implement an educational approach using online seminars, audiovisual materials, and free telemedicine services to facilitate training and counseling on stress management and adaptive coping strategies. Keywords: knowledge; pregnant women; stress level